LB3. Baricitinib plus Standard of Care for Hospitalized Adults with COVID-19 on Invasive Mechanical Ventilation or Extracorporeal Membrane Oxygenation: Results of a Randomized, Placebo-Controlled Trial. (4th December 2021) - Ely, E Wesley; Ramanan, Athimalaipet V; Kartman, Cynthia E; de Bono, Stephanie; Liao, Ran; Piruzeli, Maria Lucia B; Goldman, Jason D; Saraiva, José Francisco Kerr; Chakladar, Sujatro; Marconi, Vincent
Abstract: Background: Interventions to reduce mortality in critically ill patients with COVID-19 are a crucial unmet medical need. Baricitinib (BARI) is an oral, selective Janus kinase (JAK)1/JAK2 inhibitor with efficacy in hospitalized adults with COVID-19. Treatment with BARI 4-mg was evaluated in critically ill adult patients with COVID-19 with baseline need for invasive mechanical ventilation (IMV) or extracorporeal membrane oxygenation (ECMO). Methods: COV-BARRIER (NCT04421027) was a randomized double-blind, placebo-controlled trial in patients with confirmed SARS-CoV-2 infection and elevation of ≥ 1 serum inflammatory marker. In this newly completed substudy, enrolled participants (not previously reported) from 4 countries on IMV or ECMO at study entry were randomly assigned 1:1 to once-daily BARI 4-mg or placebo (PBO) for up to 14 days plus standard of care (SOC), which included baseline systemic corticosteroid use in 86% of patients. The prespecified exploratory endpoints included all-cause mortality and number of ventilator-free days (VFDs) through Day 28. Results: Characteristics for 101 participants are shown in Table 1. Treatment with BARI significantly reduced all-cause mortality by Day 28 compared to PBO [39.2% vs 58.0%, respectively; hazard ratio (HR) = 0.54 (95%CI 0.31, 0.96), p=0.030, relative risk (RR) = 0.68 (95%CI 0.45, 1.02); Figure 1A]. One additional death was prevented for every six BARI-treated patients. Significant reduction in mortality was also observed by Day 60 [45.1% vs 62.0%; HR = 0.56 (95%CI 0.33, 0.97), p=0.027, RR = 0.73 (95%CI 0.50, 1.06); Figure 1B]. Patients treated with BARI showed a numerical reduction in the duration of IMV and duration of hospitalization vs PBO and more BARI treated patients recovered (Table 2). No new safety findings were observed (Table 2). Conclusion: Treatment with BARI+SOC (corticosteroids) resulted in an absolute risk reduction in mortality of 19% at Day 28 and 17% at Day 60 in patients with COVID-19 who were on IMV or ECMO at enrollment. These results are consistent with the reduction in mortality observed in the less severely ill hospitalized patients in the primary COV-BARRIER study population. Disclosures: E. Wesley Ely, MD, CDC (Grant/Research Support)Eli Lilly (Other Financial or Material Support, Unpaid consultant)NIH (Grant/Research Support)VA (Grant/Research Support) Athimalaipet V. Ramanan, FRCP, AbbVie (Consultant, Speaker's Bureau)Eli Lilly and Company (Consultant, Grant/Research Support, Speaker's Bureau)Novartis (Consultant, Speaker's Bureau)Pfizer (Consultant, Speaker's Bureau)Roche (Consultant, Speaker's Bureau)Sobi (Consultant, Speaker's Bureau)UCB (Consultant, Speaker's Bureau) Cynthia E. Kartman, RN BSN, Eli Lilly and Company (Employee, Shareholder) Stephanie de Bono, MD PhD, Eli Lilly and Company (Employee, Shareholder) Ran Liao, PhD, Eli Lilly and Company (Employee, Shareholder) Maria Lucia B Piruzeli, MD, Eli Lilly and Company (Employee, Shareholder) Sujatro Chakladar, PhD, Eli Lilly and Company (Employee, Shareholder) Vincent Marconi, MD, Bayer (Consultant, Scientific Research Study Investigator)Eli Lilly (Consultant, Scientific Research Study Investigator)Gilead Sciences (Consultant, Scientific Research Study Investigator)ViiV (Consultant, Scientific Research Study Investigator)